Accounting Students' Scientific Writing Skills Viewed from Structure and Indonesian Language Rules - Aldika Putra Zega; Asril Ahmad Sani; Berqy Indah Merputi; Chikadetry Syalomita Siregar; Fadel M. Nur Siregar; Intan Juwita Purba; M Zidane Qalbin Akba; Nadia Miftahul Jannah; Olivia Fitriani; Reynaldi Surya Saputra; Perawati (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
Writing scientific papers is a crucial skill for both prospective lecturers and working professionals. Coherent writing structure and the correct application of Indonesian language norms are as important as the accuracy of its scientific content in determining the quality of a scientific paper. The purpose of this study was to assess accounting students' ability to write scientific papers, both in terms of article structure and the use of Indonesian language rules. A literature review of several relevant journals and studies published between 2021 and 2025 served as the research methodology used. According to the study's findings, accounting students' scientific writing skills remain in the low to moderate range. Key problems identified include a high percentage of spelling errors, poor choice of diction, and ineffective sentence construction. Furthermore, the application of the IMRAD format in scientific papers remains inconsistent, accompanied by weaknesses in the development of scientific arguments and inconsistencies in the use of terms in scientific papers and scientific works. These results indicate that for students to produce scientific papers that are systematic, coherent, and in accordance with standard Indonesian language rules, they require ongoing guidance through academic literacy development, project-based scientific writing training, and intensive mentoring.